THE RATE OF READING OF VISUALLY IMPAIRED STUDENTS FRONT AND BACK EYE SEGMENT. - TESKEREDŽIĆ, Amela; ALIBEGOVIĆ, Dženana Radžo (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2015)
The aim of this work was to examine existence of influence of visually impairment type on the rate of reading of visually impairment students, primary school's age, from the Centre for blind and partially sighted children and youth in Sarajevo. One minute test of laud reading is used for reading rate examination (Furlan, 1965), which makes the list of 120 words arranged from easier and shorter, to heavier and longer. We used the form C, and the result of examinees represents number of correctly read words in one minute. Results demonstrated that there is statistically evident difference within the group of visually impaired students with a different type of visual impairment. The work points out to the importance of individual approach, adaptation of working environment as well as enabling aids during education of students with a different type of visual impairment.